2006
DOI: 10.1086/508214
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 Haploinsufficiency Phenocopies 2q32-q33 Deletions, whereas Loss Suggests a Fundamental Role in the Coordination of Jaw Development

Abstract: The recent identification of SATB2 as a candidate gene responsible for the craniofacial dysmorphologies associated with deletions and translocations at 2q32-q33, one of only three regions of the genome for which haploinsufficiency has been significantly associated with isolated cleft palate, led us to investigate the in vivo functions of murine Satb2. We find that, similar to the way in which SATB2 is perceived to act in humans, craniofacial defects due to haploinsufficiency of Satb2, including cleft palate (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(186 citation statements)
references
References 29 publications
7
178
0
1
Order By: Relevance
“…Experiments performed with Satb2 knock-out (KO) mice as well as haploinsufficiency of SATB2 in humans revealed the involvement of this transcription factor in craniofacial pattern and osteoblast differentiation [26,27]. It physically interacts with both Runx2 and ATF4, eventually leading to a positive regulation of osteoblast markers [28].…”
Section: Osteoblasts: the Anabolic Cellsmentioning
confidence: 99%
“…Experiments performed with Satb2 knock-out (KO) mice as well as haploinsufficiency of SATB2 in humans revealed the involvement of this transcription factor in craniofacial pattern and osteoblast differentiation [26,27]. It physically interacts with both Runx2 and ATF4, eventually leading to a positive regulation of osteoblast markers [28].…”
Section: Osteoblasts: the Anabolic Cellsmentioning
confidence: 99%
“…[69][70][71][72] Studies have shown that SATB2 carries out a wide spectrum of biologic functions. It is a transcriptional activator of immunoglobulin l expression.…”
Section: 68mentioning
confidence: 99%
“…SATB1 does not colocalize with Xist RNA in ES cells. Single gene disruption of either SATB1 or SATB2 was compatible with female development (Alvarez et al, 2000;Britanova et al, 2006;Dobreva et al, 2006). Data of double gene disruption of SATB1 and SATB2 are currently not available.…”
Section: Higher Order Of Chromatin Structuresmentioning
confidence: 99%